Image Destination On Revisit Intention At Fotuno Rete Hot Springs In Wakumoro Village, Parigi District, Muna Regency, Southeast Sulawesi - Shaleha, Waode Maratun Shaleha; Kifli Kolewora, Riez; Faulina, Dira (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
This research aims to analyze the influence of Affective Image, Cognitive Image, and Conative Image on Revisit Intention at Fotuno Rete Spring Bath in Wakumoro Village, Parigi District, Muna Regency, Southeast Sulawesi. The population in this study consists of individuals who have visited Fotuno Rete Spring Bath twice. The sampling technique used in this study is purposive sampling, with a total sample of 40 respondents. The results of this study indicate that Affective Image, Cognitive Image, and Conative Image have a positive and significant influence on Revisit Intention at Fotuno Rete Spring Bath in Wakumoro Village, Parigi District, Muna Regency, Southeast Sulawesi